U–Pb zircon age from the radiolarian‐bearing Hitoegane Formation in the Hida Gaien Belt, Japan. (7th October 2013) - Nuramkhaan, Manchuk; Kurihara, Toshiyuki; Tsukada, Kazuhiro; Kochi, Yoshikazu; Obara, Hokuto; Fujimoto, Tatsuya; Orihashi, Yuji; Yamamoto, Koshi
Abstract: The dating of radiolarian biostratigraphic zones from the Silurian to Devonian is only partially understood. Dating the zircons in radiolarian‐bearing tuffaceous rocks has enabled us to ascribe practical ages to the radiolarian zones. To extend knowledge in this area, radiometric dating of magmatic zircons within the radiolarian‐bearing Hitoegane Formation, Japan, was undertaken. The Hitoegane Formation is mainly composed of alternating beds of tuffaceous sandstones, tuffaceous mudstones and felsic tuff. The felsic tuff and tuffaceous mudstone yield well‐preserved radiolarian fossils. Zircon grains showing a U–Pb laser ablation–inductively coupled plasma–mass spectrometry age of 426.6 ± 3.7 Ma were collected from four horizons of the Hitoegane Formation, which is the boundary between the Pseudospongoprunum tauversi to Futobari solidus–Zadrappolus tenuis radiolarian assemblage zones. This fact strongly suggests that the boundary of these assemblage zones is around the Ludlowian to Pridolian. The last occurrence of F. solidus is considered to be Pragian based on the reinterpretation of a U–Pb sensitive high mass‐resolution ion microprobe (SHRIMP) zircon age of 408.9 ± 7.6 Ma for a felsic tuff of the Kurosegawa belt, Southwest Japan. Thus the F. solidus–Z. tenuis assemblage can be assigned to the Ludlowian or Pridolian to Pragian. The present data also contribute to establishing overall stratigraphy of the Paleozoic rocks of the Fukuji–Hitoegane area. According to the Ordovician to Carboniferous stratigraphy in this area, Ordovician to Silurian volcanism was gradually reduced to change the sedimentary environment into a tropical lagoon in the early Devonian. And the quiet Carboniferous environment was subsequently interrupted, throwing it once more into the volcanic conditions in the Middle Permian.